FAKTOR MINAT BACA DALAM PEMBELAJARAN PUISI - Dina Ramadhanti; Diyan Permata Yanda (Kelasa, 2020)
AbstractOne of the factors affecting the ability to understand poetry is reading interest. Reading interest is related to attention to reading, feelings during and after reading, and responses to reading content. This research was a quantitative study with a correlational method. This study was to explain how much the reading interest factor affects the ability to understand poetry. The results showed that the relationship between the two variables was significant but not too strong based on the range of correlation values. The reading interest factor only affects the ability to understand poetry by 13.1% and the remaining 86.9% is influenced by other factors. The reading interest factor in terms of attention to reading affects the ability to understand the physical structure of the poetry, while interest in terms of feelings and responses to reading affects the ability to understand the inner structure of the poetry.Keywords: the reading interest, learning, poetry AbstrakSalah satu faktor yang mempengaruhi hasil belajar memahami puisi adalah minat baca. Minat terhadap bacaan berhubungan dengan perhatian terhadap bacaan, perasaan saat dan setelah membaca, dan respon terhadap isi bacaan. Penelitian ini merupakan penelitian kuantitatif dengan metode korelasional. Penelitian ini untuk menjelaskan seberapa besar faktor minat baca mempengaruhi kemampuan memahami puisi. Hasil penelitian menunjukkan bahwa hubungan kedua variabel signifikan tetapi tidak terlalu kuat dilihat berdasarkan rentangan nilai korelasinya. Faktor minat baca hanya mempengaruhi kemampuan memahami puisi sebesar 13,1% dan sisanya 86,9% dipengaruhi oleh faktor yang lain. Faktor minat baca dari segi perhatian terhadap bacaan mempengaruhi kemampuan memahami stuktur fisik puisi sedangkan minat dari segi perasaan dan respon terhadap bacaan mempengaruhi kemampuan memahami struktur batin puisi.Kata kunci: minat baca, pembelajaran, puisi